Potential of Sweet Potato Mutant Lines for Bioethanol Production - Amsal, Aryanti; Yuniawati, Marina; Ermayanti, Tri Muji; Mulawati, Ika (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2018)
Shoots of sweet potato Sari variety were irradiated at the doses of 0, 10, 20, 30 and 40 Gy. Irradiated shoots were planted and selected to obtain better mutant lines than that of the parent plant. Ten mutant lines were from the fourth generation which better morphology and productivity than that of the parent plant. The bestproductivity was found at mutant line number 40-2 which was 717.50 g/plant compared to parent plant with 622.50 g/plant. The highest glucose and starch content obtained were at the dose of 20 Gy which were 8.85 and 28.56 % respectively. The mutant line of Sari sweet potato has a potential to produce bioethanol. The bio-ethanol production from those of mutant lines at a range of 15.02 to 19.46 % compared to 13.67 % in the parent plant. The mutant line number 20 was the best line to produce bio-ethanol. The aim of this experiment was to find mutant lines having potential to produce bio-ethanol